Konsekwencje brexitu w dziedzinie prawa prywatnego międzynarodowego - Majkowska-Szulc, Sylwia (Problemy Prawa Prywatnego Międzynarodowego, 2020)
Brexit is a unique phenomenon as no Member State has ever expressed the will to leave the European Union. Never before had the in-depth impact of a Member State withdrawal been analysed. The issue has started to be analysed after the referendum in which the British voted in favour of leaving the European Union. The topic of the potential consequences of Brexit in the field of private international law concerns, inter alia, national jurisdiction in civil and commercial matters, mutual recognition and enforcement of judgments, specific procedures of EU uniform law, judicial cooperation between Member States or the functioning of the e-Justice Portal and dynamic forms. Before a given Member State withdraws from the EU, interested parties should have been informed, inter alia, of how pending proceedings will be conducted starting with the withdrawal day, what about proceedings initiated at the date of withdrawal or later on, and what about the rulings of the courts of the applicant state covered by the exequatur procedure before the withdrawal. Therefore, the primary purpose of the article is to determine the framework for the future relationship between the EU and the UK in the field of private international law. An additional aim of this paper is to better prepare natural and legal persons for the new post-Brexit reality. European integration has brought Europe peace and prosperity and enabled unprecedented cooperation in all areas of common interest. Following the withdrawal decision, the state and its citizens cease to benefit from the acquis communautaire. In fact, the United Kingdom left the European Union on 31 January 2020. As far as private international law is concerned, the United Kingdom has become a third country. Subsequently, on 1 February 2020 a transition period has started and it aims to provide more time for citizens and businesses to adapt. The negotiations on the future partnership between the EU and the UK has started in March 2020, but they were postponed due to the coronavirus COVID-19 pandemic. The relationship between the United Kingdom and the European Union is sometimes compared to love that has passed away, but former lovers must continue to meet from time to time to manage certain common affaires. The analysis of the topic leads to the conclusion that, in fact, Brexit is a unique phenomenon that has no added value.